Effect of detergent on alveolar particle clearance due to large tidal ventilation. Issue 2 (February 1994) - John, J; Wollmer, P; Dahlbäck, M; Jonson, B
Abstract : BACKGROUND–It has recently been shown that large tidal volume ventilation accelerates the alveolar clearance of insoluble particles and this may be related to accelerated surfactant evacuation from the alveolus into the airway. The aim of this study was to investigate if the effect of large tidal volume ventilation is modified in an experimental model of surfactant dysfunction. METHODS–Fluorescent latex particles of 0.63 microns diameter were administered in aerosol form to 30 rabbits during anaesthesia with thiopentone and mechanical ventilation. Six animals were killed immediately after aerosol administration in order to show the initial deposition of particles. Twenty four animals were divided into two groups and ventilated for three hours with either large tidal volume (mean tidal volume 30 ml/kg) or conventional ventilation (mean tidal volume 12.5 ml/kg). Six rabbits in each of the two groups were administered either the synthetic detergent dioctyl sodium sulphosuccinate in aerosol form or aerosolised vehicle. After the period of experimental ventilation the lungs were removed and dried in the expanded state. Particles in the alveolar region were counted with fluorescent microscopy in sections of the lung. RESULTS–Compared with the baseline group (mean (SD) 24.8 (9.9)) the count of residual alveolar particles was lower after large tidal volume ventilation in the absence of detergent aerosol (13.2 (6.5)). Particle count after large tidal volume ventilation and detergent treatment (23.3 (6.4)) was similar to that in the baseline group and to that in the groups exposed to conventional ventilation. CONCLUSIONS–The increase in alveolar clearance of insoluble particles caused by large tidal volume ventilation is inhibited by detergent aerosol. This might be due to reduced stability of the surfactant film after detergent aerosol.